DFT modeling of carbon incorporation in GaN(0001) and GaN(000 1 ¯ ) metalorganic vapor phase epitaxy - Kempisty, Pawel; Kangawa, Yoshihiro; Kusaba, Akira; Shiraishi, Kenji; Krukowski, Stanislaw; Bockowski, Michal; Kakimoto, Koichi; Amano, Hiroshi (Applied physics letters, 2017)
The carbon incorporation mechanism in GaN(0001) and GaN(000 1 ¯ ) during MOVPE was investigated using density functional theory (DFT) calculations. The results confirm that the crucial factors for carbon incorporation are Fermi level pinning and accompanying surface band bending. In addition, the lattice symmetry has a strong dependence on the stability of carbon in a few subsurface layers, which results from interactions between the impurities and surface states. It was shown that these effects are responsible for facilitating or hindering the incorporation of impurities and dopants. The influence of diluent gas species (hydrogen or nitrogen) on carbon incorporation was discussed.